2012
DOI: 10.3989/scimar.03610.19a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the interannual variability of the tropical Pacific as a response to an equatorial Atlantic forcing

Abstract: SUMMARY: Previous studies have reported that the tropical Atlantic has had an influence on tropical Pacific interannual variability since the 1970s. This variability is studied in the present work, using simulations from a coupled model in the Indo-Pacific but with observed sea surface temperature (SST) prescribed over the Atlantic. The interannual variability is compared with that from a control simulation in which climatological SSTs are prescribed over the Atlantic. Differences in the Pacific mean state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…In addition, both observations and ATL_VAR show strongest correlations at the beginning and the end of the 20th century, and overall weaker correlations in the middle of the century, although the phasing is somewhat different between observations and the model. Overall, the results from this analysis are consistent with the recent work by [4,10,11]. …”
Section: North Tropical Atlantic-pacific Teleconnectionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, both observations and ATL_VAR show strongest correlations at the beginning and the end of the 20th century, and overall weaker correlations in the middle of the century, although the phasing is somewhat different between observations and the model. Overall, the results from this analysis are consistent with the recent work by [4,10,11]. …”
Section: North Tropical Atlantic-pacific Teleconnectionsupporting
confidence: 82%
“…These results are consistent with what has been reported in [16]. The descending (ascending) motions in the central Pacific lead to anomalous easterlies (westerlies) in the central-western Pacific that trigger an upwelling (downwelling) oceanic Kelvin wave propagating eastward during the following months ( [9,10]). As the Kelvin wave propagates, the eastern Pacific becomes cooler (warmer) through the activation of the thermocline feedbacks and the establishment of the Bjerknes feedback ( [9]).…”
Section: Atlantic Niñosupporting
confidence: 82%
See 1 more Smart Citation
“…The model has been extensively used in climate studies regarding the teleconnections of the Tropical Atlantic (e.g. Martín-Rey et al 2012;Barimalala et al 2012;Kucharski et al 2007Kucharski et al , 2008Kucharski et al , 2009Kucharski et al , 2011Losada et al 2012;Rodriguez-Fonseca et al 2009). Rauscher et al (2011) and Herceg Bulic et al (2012) also argue that SPEEDY can be used in climate change impact studies as it is capable of simulating similar anomalies than those from complex coupled models given the appropriate boundary conditions.…”
Section: Modelsmentioning
confidence: 99%
“…Although the separated influence of the tropical Atlantic and Pacific oceans on NESA has been documented, to our knowledge there is no work tackling on the stationarity of their relationship with NESA rainfall. Moreover, recent studies have found how the Atlantic and Pacific Niños appear anticorrelated in summer during the decades after the 1970s and at the beginning of the XX century (Polo et al, 2008(Polo et al, , 2015Rodríguez-Fonseca et al, 2009;Martín-Rey et al, 2012, 2014. The concomitant action of both basins on the NESA rainfall region has not been yet explored, although important impacts have been found for the Sahel (Losada et al, 2012;Rodríguez-Fonseca et al, 2015).…”
Section: Introductionmentioning
confidence: 99%